Non-English Major Students ‘Motivation in English Classrooms: Evidence from a University Setting - Trang, Nguyen Huynh (International Journal of Educational Technology and Learning, 2021)
In learning and teaching English as a foreign language, motivation is crucial to success. The purpose of this study is to discover whether non-English-majored students are motivated in learning English and to find out what factors can help motivate them to learn English. The study mainly employed a questionnaire which is developed and administered base on Khau and Thach (2021)’s framework to collect the data. It was delivered to 54 non-English-majored students who are at their third year of study at a public university in Ho Chi Minh City, Vietnam. The results highlighted various researches that have been conducted on the elements that influence motivation. The data showed that the participants’ motivation level is at medium rank. It could be inferred that these participants were motivated to learn English at university. The current study also found that students’ motivation was mainly affected by four factors which are teacher’s personality, teacher’s methodology, facilities for studying and classmates. The results of the study contribute to the field of motivation research in EFL setting.